1,4-Dihydropyridine Antihypertensive Drugs: Recent Advances in Photostabilization Strategies - De Luca, Michele (Pharmaceutics, 2019)
The 1,4-dihydropyridine (DHP) drugs are nowadays the most used drugs in the treatment of hypertension. However, all the structures in this series present a significant sensitivity to light, leading to the complete loss of pharmacological activity. This degradation is particularly evident in aqueous solution, so much so that almost all DHP drugs on the market are formulated in solid preparations, especially tablets. The first and main process of photodegradation consists in the aromatization of the dihydropyridine ring, after which secondary processes can take place on the various substituents. A potential danger can result from the formation of single oxygen and superoxide species that can in turn trigger phototoxic reactions. Several strategies for the photostabilisation of DHP drugs have been proposed in recent years, in particular with the aim to formulate these drugs in liquid preparations, as well as to limit any toxicity problems related to light degradation. This review summarizes and describes the main aspects of the studies conducted in recent years to obtain photostable formulations of DHP drugs.